Recent progress of exosomal lncRNA/circRNA–miRNA–mRNA axis in lung cancer: implication for clinical application - Wang, Ren; Xu, Yiwei; Tong, Liangjing; Zhang, Xiao; Zhang, Sheng (Frontiers in Molecular Biosciences, 2024)
Lung cancer is the leading cause of death among malignant tumors in the world. High lung cancer mortality rate is due to most of patients diagnosed at advanced stage. The Liquid biopsy of lung cancer have received recent interest for early diagnosis. One of the components of liquid biopsy is the exosome. The exosome cargos non-coding-RNAs, especially long non-coding RNAs (lncRNAs), circular RNAs (circRNAs), and microRNAs (miRNAs). The lung cancer derived exosomal non-coding RNAs play the pivotal roles of lung cancer in carcinogenesis, diagnosis, therapy, drug resistance and prognosis of lung cancer. Given ceRNA (competitive endogenous RNA) mechanism, lncRNA or circRNA can act as ceRNA to compete to bind miRNAs and alter the expression of the targeted mRNA, contributing to the development and progression of lung cancer. The current research progress of the roles of the exosomal non-coding-RNAs and the interplay of ceRNAs and miRNAs in mediated lung cancer is illustrated in this article. Hence, we presented an experimentally validated lung cancer derived exosomal non-coding RNAs-regulated target gene axis from already existed evidence in lung cancer. Then LncRNA/circRNA-miRNA-mRNA axis may be a potential target for lung cancer treatment and has great potential in the diagnosis and prognosis of lung cancer.